Analisis Peran Aplikasi Go-Food terhadap Perilaku Konsumen (Studi pada Merchant Parjo Semarang) - Akhmad Faizul Umam; Ari Pradhanawati; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2022)
Abstract: The mobile phone market share in Indonesia is quite large, followed by many applications that contain many features in order to attract consumers. One of the applications includes GoJek which contains the Go-Food feature in the application. The Go-Food application helps a lot with merchant sales. Currently, Parjo Semarang is included in the Top Destination merchant that is in demand by consumers in the city of Semarang. However, another impact of often someone or group using the Go-Food application is to make individuals or groups become a common activity and cause laziness of individuals / groups in carrying out activities out looking for or buying their own.This study is to determine the role of the Go-Food application in changing consumer behavior in Parjo Semarang. In the variables of changes in consumer behavior, it is influenced by the decision-making process in purchasing, namely regarding problems, finding information, evaluating alternatives, buying decisions, post-purchase evaluation. The frame of mind in this study is Schiffman and Kanuk about the stages of the purchasing decision-making process. these stages will be an analytical tool in answering research. The research method used is a qualitative approach using data collection techniques in the form of interviews and observations. Interviews were conducted with 3 sources, namely consumers who use the Go-Food application, Go-Food driver partners and Go-Food parjo semarang merchant partners.The results of this study show that there is a change in behavior in the role of the Go-Food application on consumer behavior in Parjo Semarang. In the stage of taking the decision of the purchase produces two positive and negative factors.